Penerapan Metode Gabor Wavelet Dalam Pengenalan Wajah Pada Rekaman CCTV - Sofi Andianis Fau; Sinar Sinurat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Human facial recognition is an important field of research, and there are many applications today that can apply it. Through the development of a technique such as the Gabor Wavelet, computers can now outpace the human brain in a variety of tasks in facial recognition, particularly those that require searching large facial databases. The face recognition system is used to compare an input face image with a face database and produce the face that best matches that image if detected. Meanwhile, face authentication is used to test the authenticity / similarity of a face with face data that has been stored in the previous database. Applications have advantages over conventional methods. In case it is not easily stolen or used by unauthorized users. The purpose of this final project is to create a facial recognition software from CCTV footage using Gabor Wavelet to reduce the dimensions of facial images as well as to determine the capabilities of the technique. In this final project, the software created uses a still image as input. To build this application using Matlab. The system test results show that the use of Gabor Wavelet for facial recognition on CCTV footage provides a fairly high level of accuracy. Test results The results obtained will then be entered into the Gabor Wavelet Method to determine the identity of the face owner. For facial images that were included in the exercise, it was possible to get 85.71% correct identification